The implementation of family group conferences in the child - and youth - care system in Austria/Carinthia - challenges and benefits - Höllmüller, Hubert (Ревија за социјална политика/Journal of Social Policy, 2019)
“Family group conference” is a new and radical method of participating in the family system in the process of care planning within the public child- and youth-care. After the federal county of Lower Austria, Carinthia is preparing to implement a “family group conference” in the child - and youth-care system. The experiences from Lower Austria are well documented by two research projects, so it is possible to draw conclusions about things that function and those that cause problems in the process of implementation. The first family group conferences already started in Carinthia and the first interviews with families und social workers of the youth welfare office were realized this year. Therefore, it is possible to take the first look on experiences. Within the 13th Family Group Conference Network held in Klagenfurt in the beginning of September, with about 100 participants from Germany, Switzerland and Austria, the issues about the necessary and most effective steps for the formal implementations in Carinthia could be discussed, so that a clear procedure would be defined. The main issue in any process of implementation is the paradigmatic shift in the attitudes of the professionals from an expert system to cooperative and participative understanding of family situations within the frame of child protection.